Relationships between Emotional Intelligence, Professional Effectiveness, and Professional Quality of Life in Novice Counseling Psychologists - Pankratova, A.A.; Nikolaeva, M.E. (Psihologo-pedagogičeskie issledovaniâ, 2022)
The article examines how emotional intelligence (EI) is associated with professional performance and professional quality of life (satisfaction and fatigue) in counseling psychologists. Fifty-four counseling psychologists (83% female) aged from 23 to 48 years (M=36; SD=6) with counselling experience from 1 to 5 years (M=2; SD=1) took part in the study. The participants assessed the effectiveness of their consultation during the training session using SRS (Session Rating Scale) by Miller, Duncan, and Johnson (together with the client). In addition, they filled out the EmIn questionnaire by Lyusin, the TEIQue (Trait Emotional Intelligence Questionnaire) by Petrides and Furnham, and the ProQOL (Professional Quality of Life) scale by Stamm. It was found that (1) counselor’s EI measured by TEIQue, self-efficacy in establishing contact with a client, and self-criticism correlate positively with the client's estimates of counselling effectiveness; (2) the better the counselor understands her own emotions and manages them, the higher her self-efficacy; on the contrary, the better the counselor understands other people's emotions, the lower her self-efficacy and the higher her self-criticism; (3) counselors with a higher level of EI have a better professional quality of life, namely, higher compassion satisfaction and lower compassion fatigue scores. EI is considered as a professionally important quality for counseling psychologists. In addition, the predictive qualities of the TEIQue and EmIn questionnaires are discussed. В статье анализируется, как эмоциональный интеллект (ЭИ) связан с эффективностью деятельности и качеством профессиональной жизни (удовлетворенностью и утомлением) у психологов-консультантов. В исследовании приняли участие 54 психолога-консультанта (83% женщины) в возрасте от 23 до 48 лет (M=36; SD=6) и со стажем консультативной работы от 1 года до 5 лет (M=2; SD=1). Участники оценивали эффективность проведенной ими консультации в рамках учебной сессии с помощью шкалы SRS (Session Rating Scale) С. Миллера, Б. Дункана, Л. Джонсон (совместно с клиентом), а также заполняли опросники ЭмИн Д.В. Люсина, TEIQue (Trait Emotional Intelligence Questionnaire) К. Петридеса, А. Фернхема, ProQOL (Professional Quality of Life) Б. Стамм. Было установлено, что: 1) ЭИ (по опроснику TEIQue), самоэффективность при установлении контакта с клиентом и критичность консультанта положительно коррелируют с эффективностью консультирования по оценкам клиента; 2) чем лучше консультант понимает свои эмоции и управляет ими, тем выше его самоэффективность, а чем лучше консультант понимает эмоции других людей, тем, напротив, ниже его самоэффективность и выше критичность; 3) у консультантов c более высоким уровнем ЭИ выше показатели по удовлетворенности профессиональной деятельностью и ниже показатели по утомлению от сочувствия. ЭИ рассматривается как профессионально важное качество для психологов-консультантов, кроме этого, обсуждаются прогностические возможности опросников TEIQue и ЭмИн.